(untitled) (AYUSHDHARA, 2021)
Sinusitis is defined as the inflammation of the mucosa either of any one or all of the paranasal sinuses. In humans, there are four paired sinuses which are termed as paranasal sinuses and they are maxillary, frontal, ethmoid and sphenoid sinuses. Ayurveda being an ancient holistic science aims at alleviating the disease and protection and prevention of the positive health. Shalakya Tantra is one of the Astangas of Ayurveda that deals with the Uttamanga and the diseases related to Urdhvajatru. Paranasal sinusitis, the most common disease in Shalakya tantra can be correlated to the disease Apeenasa, Peenasa, Dusta Pratishyaya etc in Ayurveda based on its signs and symptoms. Apeenasa and Peenasa are used interchangeably for paranasal sinusitis in Ayurveda and they are managed with Deepana Pachana, Vamana, Virechana, Dhumapana, Nasya Karma or Shirovirechana. Nasya Karma, one of the Panchakarma therapy and the best therapy for the Urdhwajatrugata Rogas plays a vital role in the successful management of the sinusitis. In this therapy, the medicine is administered through nose either in the form of ghee, oil, powder, liquid or smoke. It is particularly useful in the treatment of diseases occurring in the organs situated above the clavicle but indirectly it works on the whole body by improving the functioning of the endocrine glands and nervous system.